Development Of Bismuth Particles Modified Electrodes For Heavy Metal Sensors - Liew, Xian Yun (Universiti Sains Malaysia, 2018)
In this study, bismuth (Bi) particles were synthesised and grew directly on Indium Tin Oxide (ITO) electrode using the hydrothermal method. The synthesised Bi particles were deposited on indium tin oxide coated polyethylene terephthalate (ITO-PET) electrodes. The effect of hydrothermal reaction period was studied (5, 6, 7 and 8 hours).Characterisation of Bi particles were performed using X-ray Diffractometer (XRD) and Field Emission Scanning Electron Microscopy (FESEM). The properties of bismuth modified ITO electrodes (Bi/ITO) were characterised using XRD and Tabletop SEM. XRD analysis of Bi particles showed that Bi with Rhomboheral structure of R-3m space group (JCPDS card no.: 00-005-0519) were obtained for all samples. For Bi/ITO, the XRD results showed the present of Bi with Rhomboheral structure of R-3m space group (JCPDS card no.: 00-005-0519) and bismuth oxide (Bi2O3) of monoclinic crystal of P21/c space group (JCPDS card no.: 00-014-0699). The results were further proven by Tabletop SEM which showed the presence of black Bi particles and white Bi2O3 particles. The size of the synthesised Bi powders with varying hydrothermal reaction period were in the range of 76 nm to 224 nm. The synthesised Bi particles were then drop casted on ITO-PET electrode before subjected to cyclic voltammetry (CV) and differential pulse anodic stripping voltammetry (DPASV) analysis. The effective surface area of Bi/ ITO-PET electrode is larger than effective surface area of Bi/ITO, thus giving higher sensitivity. The limit of detection of Pb(II) was 12.29 g/L. Pb(II) was detected at potential of -0.736V in multi-element standard solution for interference studies.